High-efficiency preparation of zircon ceramics using borosilicate glass as sintering additive. Issue 15 (1st August 2022) - Li, Jiajing; Xian, Qiang; Li, Zhen; Chen, Zhenyu; Zhang, Xuanrui; Chen, Qiaolin; Dan, Hui; Ding, Yi; Duan, Tao
Abstract: Synthesis of zircon (ZrSiO4 ) ceramics suffers from high sintering temperature and long holding time. Herein, we reported a novel method to synthesize ZrSiO4 ceramics using borosilicate glass as sintering additive, and the influences of the borosilicate glass content and sintering temperature on the phase evolution and microstructure of the obtained ceramics were investigated in detail. The results indicated that the addition of borosilicate glass had significant effect on the phase evolution and properties of the obtained ceramics. The formation of ZrSiO4 was enhanced with increasing the content of borosilicate glass and sintering temperature. At sintering temperature of 1400 °C and holding time of 6 h, the formation efficiency of ZrSiO4 phase was up to 91.27 wt%. Moreover, ZrSiO4 ceramic with high compactness was obtained with the weight ratio of borosilicate glass to zircon in the range of 0–0.25. The results demonstrated that ZrSiO4 ceramics can be effectively prepared by using borosilicate glass as sintering additive.